HUBUNGAN TINGKAT KECEMASAN DENGAN MEKANISME KOPING PADA PASIEN GAGAL JANTUNG KONGESTIF DI RSU PANDAN ARANG BOYOLALI - Atina Inayah Ihdaniyati; Winarsih Nur Ambarwati (Jurnal Berita Ilmu Keperawatan, 2008)
Background : Anxiety on congestive heart failure patient resulted because they experience out of breath and chest pain so they tend to concerned. Anxiety could motivate the individual to appropriate with to stressor and conduct an action to correct it. Coping mechanism is the result of an individual action to face of the stressor. When individual could face the stressor very well, it will deliver the adaptive coping. But when individual unable to find the good solution, it will conduct the maladaptive coping. Target of research : To know the relation between anxiety level with the coping mechanism on congestive heart failure patient. Research method : This Research has the non-experimental character with the descriptive method of correlation use the cross sectional approach. Sampling techniques which used are accidental sampling with the total samples are 30 responders. Validity test use the Product Moment test and reliability test use the Alpha Cronbach test. For data analysis, it uses the Kendal tau-b test with test of normality data use the z test. Result of research : Result of Kendal tau-b correlation analysis indicate that the count value equal to -0,745 with the probability 0,000 (p z table . The results indicate that there is a capable and significant of negative relation between anxiety level with the coping mechanism.